Clodia metelli;the tribune's sister. - Marilyn B. Skinner (Women in antiquity., 2011)
Clodia Metelli: The Tribune's Sister is the first full-length biography of a Roman aristocrat whose colorful life, as portrayed by contemporaries, has inspired numerous modern works of popular fiction, art, and poetry. This study, by examining the way in which she was represented, sheds light on the role played by major female figures in Roman literature.